USM IEEE SB WON 1ST PRIZE IN INFOGRAPHICS COMPETITION 2016 - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
PENANG, 16 October 2016 Universiti Sains Malaysia (USM) has been put in the limelight again when students from the USM School of Electrical and Electronic Engineering won the 1st prize in IEEE Malaysia Student Congress 2016 Student Branch Infographics Competition yesterday, held in Kuala Lumpur.